2023
DOI: 10.1101/2023.02.10.528086
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conserved Chamber-Specific Polyploidy Maintains Heart Function inDrosophila

Abstract: Developmentally programmed polyploidy (whole-genome-duplication) of cardiomyocytes is common across evolution. Functions of such polyploidy are essentially unknown. Here, we reveal roles for precise polyploidy levels in cardiac tissue. We highlight a conserved asymmetry in polyploidy level between cardiac chambers in Drosophila larvae and humans. In Drosophila, differential Insulin Receptor (InR)sensitivity leads the heart chamber to reach a higher ploidy/cell size relative to the aorta chamber. Cardiac ploidy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 136 publications
0
2
0
Order By: Relevance
“…Functional enrichment analyses of human genes based on Database for Annotation, Visualization and Integrated Discovery (DAVID) Bioinformatics Resources (Huang et al, 2009a, 2009b) show that they are enriched in many processes involved in cardiac muscle organization and contraction, such as dilated cardiomyopathy, cardiac muscle contraction, cyclase‐related activities, contractile fiber, and myofibril (Figure 3a). Recent research in humans has reported that transcriptional differences between atrial and ventricular cardiomyocyte populations suggest distinct developmental origins, unique hemodynamic influences, and specialized functions within cardiac chambers (Chakraborty et al, 2023). Additionally, cardiomyocytes are more prevalent in ventricles compared to atria, indicating a higher proportion of these cells in the ventricular region (Litviňuková et al, 2020; Tucker et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Functional enrichment analyses of human genes based on Database for Annotation, Visualization and Integrated Discovery (DAVID) Bioinformatics Resources (Huang et al, 2009a, 2009b) show that they are enriched in many processes involved in cardiac muscle organization and contraction, such as dilated cardiomyopathy, cardiac muscle contraction, cyclase‐related activities, contractile fiber, and myofibril (Figure 3a). Recent research in humans has reported that transcriptional differences between atrial and ventricular cardiomyocyte populations suggest distinct developmental origins, unique hemodynamic influences, and specialized functions within cardiac chambers (Chakraborty et al, 2023). Additionally, cardiomyocytes are more prevalent in ventricles compared to atria, indicating a higher proportion of these cells in the ventricular region (Litviňuková et al, 2020; Tucker et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…After more significant tissue loss, an increase in iEC size can also regenerate tissue mass in a process called compensatory cellular hypertrophy (CCH). 1,5,7,10,[13][14][15][16][17][18] In contrast, other evidence indicates that in some contexts polyploidy can restrict regeneration. 1,5,[19][20][21][22][23][24] Recently, there has been an intense interest in the contribution of iECs to cancer therapy resistance and cancer relapse.…”
Section: Introductionmentioning
confidence: 99%